The Impact of Entrepreneurship Spaces in Higher Vocational Colleges on Students’ Entrepreneurial Intentions-Taking Creativity as the Mediating Variable - Li, Da Ang; Liao, Chang Chun (Journal of Ecohumanism, 2024)
This journal article examines the influence of entrepreneurship spaces, also known as maker spaces, in higher vocational colleges on students' entrepreneurial intentions. It specifically focuses on the mediating role of creativity in this relationship. The study reviews existing literature on the significance of entrepreneurship spaces in fostering entrepreneurial intentions and emphasizes the importance of creativity as a precursor to entrepreneurial thinking. Additionally, it discusses the role of maker spaces in shaping students' attitudes towards entrepreneurship and their willingness to engage in entrepreneurial activities. The findings of the study indicate that maker spaces have a positive impact on students' entrepreneurial intentions, and creativity plays a crucial role in mediating this relationship. Maker spaces provide students with resources, mentorship, and a supportive community, which fosters a pro-entrepreneurial mindset and enhances self-efficacy in entrepreneurship. These spaces also simulate real-world entrepreneurial experiences, reducing barriers to entry and increasing students' willingness to pursue entrepreneurial endeavours. Creativity is identified as a key mechanism through which entrepreneurship spaces influence students' entrepreneurial thinking. Maker spaces stimulate innovative thinking, problem-solving, and idea generation, creating a creative environment that fuels entrepreneurial intentions. Therefore, fostering creativity within these spaces is crucial for nurturing entrepreneurial intentions among students and preparing them for the evolving business landscape. The article concludes by emphasizing the importance of understanding the interplay between entrepreneurship spaces, creativity, and entrepreneurial intentions for designing effective entrepreneurship education programs and optimizing the impact of maker spaces in higher vocational colleges. It suggests that future research should explore contextual variations, long-term effects, curriculum integration, inclusivity, interdisciplinary collaboration, mentorship and support networks, measurement and assessment tools, collaborative research, and policy implications of entrepreneurship spaces in higher vocational colleges.